Identifying etiologies of heart failure using non-contrast cardiac magnetic resonance imaging: cine imaging, T1 and T2 mapping, and texture analysis for T1 mapping - Amano, Yasuo; Suzuki, Yasuyuki; Tang, Xiaoyan; Ando, Chisato (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThe aim of this retrospective study was to evaluate the usefulness of non-contrast cardiac magnetic resonance imaging, including cine imaging, T1 and T2 mapping, and texture analysis for T1 mapping, for identifying etiologies of heart failure (HF).MethodsForty-seven patients with HF were examined using a 1.5 T scanner. Cine imaging parameters and native T1 and T2 values at the mid-septal segment were measured. Vertical run length nonuniformity, vertical gray level nonuniformity (vGLNU), wavelet energy LL(3) and HH (4) on T1 mapping were estimated at the mid-septal segment using open-access software. Late gadolinium enhancement was investigated to help diagnose the etiologies of HF. We used Kruscal-Wallis’ with a post-hoc Steel-Dwass' test, Wilcoxon signed-ranked test, Pearson's chai square test and receiver operator curve analysis (ROC) to assess the usefulness of non-contrast CMR for identifying etiologies of HF.ResultsThere were significant differences in left ventricular end-diastolic volume (LVEDV) indexed to body surface area (LVEDVi), left ventricular myocardial mass/LVEDV, native T1, and vGLNU between dilated cardiomyopathy (DCM), hypertensive cardiomyopathy (HC) and tachycardia-induced cardiomyopathies (TIC). DCM had higher T1 and lower vGLNU than HC. When compared with TIC, DCM showed significantly higher LVEDV and LVEDVi. ROC analysis revealed that LVEDV and vGLNU provided high specificity for differentiating DCM from the other etiologies.ConclusionNative T1 mapping and its texture analysis may be valuable for differentiating between DCM and HC. Cine imaging can be useful for differentiating between DCM and TIC.